Acceptance and Adoption of Protective Measures During the COVID-19 Pandemic: The Role of Trust in Politics and Trust in Science - Simone Dohle; Tobias Wingen; Mike Schreiber (Social Psychological Bulletin, 2020)
The United Nations have described the outbreak of the coronavirus disease 2019 (COVID-19) as the worst global crisis since the second world war. Behavioral protective measures, such as good hand hygiene and social distancing, may strongly affect infection and fatality rates worldwide. In two studies (total N = 962), we aimed to identify central predictors of acceptance and adoption of protective measures, including sociodemographic variables, risk perception, and trust. We found that men and younger participants show lower acceptance and adoption of protective measures, suggesting that it is crucial to develop targeted health messages for these groups. Moreover, trust in politics and trust in science emerged as important predictors for the acceptance and adoption of protective measures. These results show that maintaining and ideally strengthening trust in politics and trust in science might be central for overcoming the COVID-19 pandemic.